Disulfide Biochemistry in 2-Cys Peroxiredoxin: Requirement of Glu50 and Arg146 for the Reduction of Yeast Tsa1 by Thioredoxin - Tairum, Carlos A. [UNESP]; Oliveira, Marcos A. de [UNESP]; Horta, Bruno B.; Zara, Fernando Jose [UNESP]; Netto, Luis E. S. (Academic Press Ltd Elsevier B.V. Ltd, 2012)
2-Cys peroxiredoxin (Prx) enzymes are ubiquitously distributed peroxidases that make use of a peroxidatic cysteine (Cys(P)) to decompose hydroperoxides. A disulfide bond is generated as a consequence of the partial unfolding of the alpha-helix that contains Cys(P). Therefore, during its catalytic cycle, 2-Cys Prx alternates between two states, locally unfolded and fully folded. Tsa1 (thiol-specific antioxidant protein 1 from yeast) is by far the most abundant Cys-based peroxidase in Saccharomyces cerevisiae. In this work, we present the crystallographic structure at 2.8 angstrom resolution of Tsa1(C47S) in the decameric form [(alpha(2))(5)] with a DTT molecule bound to the active site, representing one of the few available reports of a 2-Cys Prx (AhpC-Prx1 subfamily) (AhpC, alkyl hydroperoxide reductase subunit C) structure that incorporates a ligand. The analysis of the Tsa1(C47S) structure indicated that G1u50 and Arg146 participate in the stabilization of the Cys(P) alpha-helix. As a consequence, we raised the hypothesis that G1u50 and Arg146 might be relevant to the Cys(P) reactivity. Therefore, Tsa1(E50A) and Tsa1(R146Q) mutants were generated and were still able to decompose hydrogen peroxide, presenting a second-order rate constant in the range of 10(6) M-1 S-1. Remarkably, although Tsa1(E50A) and Tsa1(R146Q) were efficiently reduced by the low-molecular-weight reductant DTT, these mutants displayed only marginal thioredoxin (Trx)-dependent peroxidase activity, indicating that G1u50 and Arg146 are important for the Tsa1-Trx interaction. These results may impact the comprehension of downstream events of signaling pathways that are triggered by the oxidation of critical Cys residues, such as Trx. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: peroxiredoxin; Saccharomyces cerevisiae; crystal structure; thioredoxin; protein-protein interactions